Mapping of Novel QTL Regulating Grain Shattering Using Doubled Haploid Population in Rice (Oryza sativa L.) - Gyu-Ho Lee; In-Kyu Kang; Kyung-Min Kim (International Journal of Genomics)
The critical evolutionary step during domestication of major cereals was elimination of seed shattering because the easy-to-shatter trait in wild relatives results in a severe reduction in yield. In this study, we analyzed the QTLs associated with shattering employing a high-density genetic map in doubled haploid (DH) population of rice (Oryza sativa L.). A genetic linkage map was generated with 217 microsatellite markers spanning 2082.4 cM and covering 12 rice chromosomes with an average interval of 9.6 cM between markers based on 120 DHLs derived from a cross between Cheongcheong indica type cultivar and Nagdong japonica type cultivar. In the QTL analysis, five QTLs pertaining to the breaking tensile strength (BTS) were detected in 2013 and 2015. Two regions of the QTLs related to BTS on chromosome 1 and chromosome 6 were detected. Several important genes are distributed in 1 Mbp region of the QTL on chromosome 6 and they are related to the formation of abscission layer. We decide to name this QTL qSh6 and the candidate genes in the qSh6 region can be employed usefully in further research for cloning.